Antinociceptive and Anti-Inflammatory Effects of Zerumbone against Mono-Iodoacetate-Induced Arthritis - Chien, Ting-Yi (Int J Mol Sci, 2016)
The fresh rhizome of Zingiber zerumbet Smith (Zingiberaceae) is used as a food flavoring and also serves as a folk medicine as an antipyretic and for analgesics in Taiwan. Zerumbone, a monocyclic sesquiterpene was isolated from the rhizome of Z. zerumbet and is the major active compound. In this study, the anti-inflammatory and antinociceptive effects of zerumbone on arthritis were explored using in vitro and in vivo models. Results showed that zerumbone inhibited inducible nitric oxide (NO) synthase (iNOS), cyclooxygenase (COX)-2 expressions, and NO and prostaglandin E(2) (PGE(2)) production, but induced heme oxygenase (HO)-1 expression in a dose-dependent manner in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. When zerumbone was co-treated with an HO-1 inhibitor (tin protoporphyrin (SnPP)), the NO inhibitory effects of zerumbone were recovered. The above results suggest that zerumbone inhibited iNOS and COX-2 through induction of the HO-1 pathway. Moreover, matrix metalloproteinase (MMP)-13 and COX-2 expressions of interleukin (IL)-1β-stimulated primary rat chondrocytes were inhibited by zerumbone. In an in vivo assay, an acetic acid-induced writhing response in mice was significantly reduced by treatment with zerumbone. Furthermore, zerumbone reduced paw edema and the pain response in a mono-iodoacetate (MIA)-induced rat osteoarthritis model. Therefore, we suggest that zerumbone possesses anti-inflammatory and antinociceptive effects which indicate zerumbone could be a potential candidate for osteoarthritis treatment.